Why did the Epistolary Novel Go Out of Fashion? - Sergey N. Zenkin (Литературный факт)
The epistolary novel, extremely popular in European literature of the 17th‒18th centuries, nearly disappeared from the literary horizon in the middle of the 19th century and subsequently was used mainly in metaliterary and parodic functions. This article attempts to explain this change by fitting it into the general process of restructuring the European novel in the “epoch of realism.” Three aspects of this process stand out. On the sociocultural level, this is the collapse of aristocratic society, which was mainly depicted in the classic epistolary novel and left its mark on it in the “noble” style of letters, focused on the life and habits of the women of high society. On the narratological level, this is a complication of the theatrical structures of the novel: the verbal exchange of the characters is transferred from the external composition (letters forming the text of the novel) to the internal one (oral “scenes”), and the 19th-century novel privileges the form of personal diary the texts of which, unlike letters, are not designed to have an impact on the recipient. Finally, on the aesthetic level, this is a change in the prevailing receptive mode: instead of testimony, which presupposes the authority of intermediary characters (for instance, writing persons in correspondence), the 19th-century novel strives for an impersonal illusion and a direct “fictional immersion” of the reader in the moving world of the work, for example in the process of unveiling something hidden (in a mystery novel, detective story).